2009
DOI: 10.1017/s0960129508007342
|View full text |Cite
|
Sign up to set email alerts
|

Unary automatic graphs: an algorithmic perspective

Abstract: 1This paper studies infinite graphs produced from a natural unfolding operation applied to finite graphs. Graphs produced via such operations are of finite degree and automatic over the unary alphabet (that is, they can be described by finite automata over unary alphabet). We investigate algorithmic properties of such unfolded graphs given their finite presentations. In particular, we ask whether a given node belongs to an infinite component, whether two given nodes in the graph are reachable from one another,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In particular, when the automaton is fixed, deciding if there is a path from vertex x to vertex y takes linear time in x and y. Furthermore, [7] showed that connectedness of unary automatic graphs of finite degrees is decidable in O(n 3 ) time and the following result which we will use later.…”
Section: Graphs Of Finite Degreementioning
confidence: 91%
See 3 more Smart Citations
“…In particular, when the automaton is fixed, deciding if there is a path from vertex x to vertex y takes linear time in x and y. Furthermore, [7] showed that connectedness of unary automatic graphs of finite degrees is decidable in O(n 3 ) time and the following result which we will use later.…”
Section: Graphs Of Finite Degreementioning
confidence: 91%
“…Therefore, the membership problem is decidable in linear time. In [7], Khoussainov, Liu, and Minnes investigated a range of algorithmic properties of unary automatic graphs of finite degree. For example, they showed that the reachability problem for unary automatic graphs of finite degree can be decided in polynomial time in the sizes of the input vertices and the automaton.…”
Section: Graphs Of Finite Degreementioning
confidence: 99%
See 2 more Smart Citations
“…Deciding these questions by a translation of monadic second-order formulae yields very slow algorithms (non-elementary complexity). Khoussainov, Liu and Minnes [11] exploited structural properties of unary automatic graphs with finite degree to solve these questions in polynomial-time.…”
Section: Introductionmentioning
confidence: 99%